Congenital pseudoaneurysm of the mitral–aortic intervalvular fibrosa: a case report. (29th May 2017) - Harrington, Jamie K.; Glickstein, Julie; Shah, Amee
Abstract: The mitral–aortic intervalvular fibrosa is an area of fibrous continuity between the mitral and aortic valves. We present the first case of a congenital pseudoaneurysm in this region, detected prenatally as an isolated cardiac defect, which was followed-up conservatively postnatally. The diagnosis was confirmed by echocardiogram demonstrating blood flow into the pouch during systole and into the left ventricular outflow tract during diastole. The infant has been followed-up with serial echocardiograms demonstrating stable size and appearance of the lesion, without signs of obstruction, making close continued observation a reasonable approach.